Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1540-8175.2011.01410.x
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Function in Hypertension: New Insight by Speckle Tracking Echocardiography

Abstract: In hypertensive patients, STE provides more detailed information than conventional echocardiography and TDI, since it reveals a systolic dysfunction before hypertrophy occurs (Stage A of ACC/AHA classification of HF) and identifies some early LV mechanic changes that might improve the clinical management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
4
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 53 publications
11
101
4
5
Order By: Relevance
“…Therefore, we deduced there were more remarkable myocardial damages in EP. Notably, GLS in hypertension is reported as the first to be impaired in subclinical LV damage and GCS in hypertensive heart disease is recognized as compensatory mechanism acting to prevent a failure of systolic function in the presence of a subendocardial damage with longitudinal function impairment [22]. However, in our study, there was no significant change in GLS and the value of GCS was higher in LP vs. EP.…”
Section: Discussionmentioning
confidence: 42%
“…Therefore, we deduced there were more remarkable myocardial damages in EP. Notably, GLS in hypertension is reported as the first to be impaired in subclinical LV damage and GCS in hypertensive heart disease is recognized as compensatory mechanism acting to prevent a failure of systolic function in the presence of a subendocardial damage with longitudinal function impairment [22]. However, in our study, there was no significant change in GLS and the value of GCS was higher in LP vs. EP.…”
Section: Discussionmentioning
confidence: 42%
“…47 Similar alterations in LV GLS with preservation of radial and circumferential deformation have been described in systemic hypertension, indicating that an abnormal pattern of LV deformation results from afterload-induced myocardial hypertrophy. 51 Normal ranges for CMR-FT indices in the pediatric age group considering age, sex, and allometry have become recently available. 52 More studies correlating CMR-FT indices with clinical outcomes are needed in pediatric and adult CHD imaging.…”
Section: Applications In Chdmentioning
confidence: 99%
“…Newer echocardiography methods such as speckle tracking echocardiography (STE) allow robust assessment of the longitudinal shortening that is predominantly influenced by subendocardial fibres and is more suited to detect subtle myocardial damage. 9 Recently, Adda et al 10 reported markedly reduced LV longitudinal shortening in patients with PLF: a finding that may help explain the underlying pathophysiological mechanisms. In the application of STE analysis to the left atrium, three separate components 11 can be characterized: reservoir function, conduit function, and active LA contraction ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%